THE IMPACT OF MODERATION OF PRICE DISCOUNTS: BRAND IMAGE AND E-WOM ON PURCHASE DECISIONS - Fikriyah, Nur Laili; Baiturrohman, Baiturrohman; Nur Afifah, Yans (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
This study aims to examine the influence of brand image and electronic Word of Mouth (E-WOM) on purchasing decisions, and the moderating influence of price discount variables. This study uses a quantitative approach with a survey method on Shopee-food Mie Gacoan consumers aged 18-35 years. The sampling technique used purposive sampling with a total of 230 respondents. In this study, data was managed and analyzed using the Smart-PLS 3.0 application. The tests carried out were validity and reliability tests, model suitability tests, and hypothesis tests. The results of this study are that brand image has a significant influence on purchasing decisions. Electronic Word of Mouth (E-WOM) has a significant influence on purchasing decisions. The next result is that price discounts do not moderate brand image and Electronic Word of Mouth (E-WOM) on purchasing decisions. In line with previous studies, price discounts do not have a significant moderating influence on purchasing decisions. Based on the results of this study, it shows that it is in line with previous studies and provides additional references for further research.